Psychological Support in Sport Injury Rehabilitation: Evidence from Physiotherapists and Athletes - Monna Arvinen-Barrow; Jim Berry; Carine Luxama (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the role of psychological interventions in sports injury rehabilitation by exploring physiotherapists’ and athletes’ perspectives and identifying the effectiveness of psychological support within contemporary sports medicine rehabilitation practices. Methodology: This study used a mixed-methods design involving a national survey of 361 licensed physiotherapists in the UK, a training preference survey (N=22), and semi-structured interviews analyzed using Interpretative Phenomenological Analysis. Data were supported by contemporary literature review in sport psychology and sports medicine up to 2025. Main Findings: The findings revealed that most physiotherapists recognized the importance of psychological aspects in rehabilitation but lacked formal training in applying psychological interventions systematically. Goal setting, social support, and imagery were the most frequently applied interventions, while relaxation and positive self-talk were less utilized. Athletes emphasized emotional acknowledgment and psychological support from physiotherapists as essential factors during recovery. Novelty/Originality of this study: This study integrates empirical findings from physiotherapists and injured athletes with recent developments in sport psychology and sports medicine literature up to 2025. It highlights the urgent need for systematic psychological competency training in sports physiotherapy and proposes a comprehensive biopsychosocial rehabilitation framework to improve athlete recovery outcomes.